Stewardship of Patient Genomic Data: A Policy Statement of the American College of Medical Genetics and Genomics (ACMG). Issue 9 (September 2022) - Best, Robert G.; Khushf, George; Rabin-Havt, Sara Schonfeld; Clayton, Ellen Wright; Grebe, Theresa A.; Hagenkord, Jill; Topper, Scott; Fivecoat, Jaime; Chen, Margaret; Grody, Wayne W.
Abstract : (Abstracted from Genet Med 2022;24:509–511) The need for genomic research is a firmly held value of the American College of Medical Genetics and Genomics (ACMG), as this can lead to discovery for the improvement of health outcomes and patient experience. However, an exchange of deidentified genomic data presents a potential opportunity for breach of privacy.